Coaching and Education of Sepak Takraw Sports: an Evaluation Study - Padli; Yanuar Kiram; Jeki Haryanto; Muhammad Arie Desman; Vega Soniawan; Nova Sesarina Sembiring (Jurnal Pendidikan dan Pengajaran, 2023)
The importance of this research is to examine the implementation of sports coaching. This study aims to evaluate the implementation of sports training. This study encourage government of sports education and training so as to help the government know how the progress of athletes in sports training centers as an effort to advance, improve and nurture athletes who are capable of takraw to the international level. This study uses a context evaluation approach that refers to the CIPPO model with the method used is a mixed method with an explanatory model. The number of research samples is 25 athletes, coaches, stakeholders, KONI and PSTI sepak takraw using simple random sampling technique. The data collection instruments used were questionnaires, interviews, observations, and instrument documentation. Analysis of the questionnaire data conducted by researchers using descriptive statistics. Meanwhile, data analysis from interviews was conducted with Miles & Huberman. With the results and conclusions of the study that sepak takraw athletes still experience several obstacles in increasing their capacity as professional athletes to compete in the international arena, they do require several solutions and strategies from the government and other supporters.